Dominant LMNA mutations can cause combined muscular dystrophy and peripheral neuropathy. Issue 7 (16th June 2005) - Benedetti, S; Bertini, E; Iannaccone, S; Angelini, C; Trisciani, M; Toniolo, D; Sferrazza, B; Carrera, P; Comi, G; Ferrari, M; Quattrini, A; Previtali, S C
Abstract : The coexistence of neurogenic and myogenic features in scapuloperoneal syndrome is rarely ascribed to a single gene. Defects in the nuclear envelope protein lamin A/C, encoded by the LMNA gene, have been shown to be associated with a variety of disorders affecting mainly the muscular and adipose tissues and, more recently, with autosomal recessive Charcot–Marie–Tooth type 2 neuropathy. This report is about a patient presenting features of myopathy and neuropathy due to a dominant LMNA mutation, suggesting that the peripheral nerve might be affected in primary LMNA myopathy. Our observations further support the marked intrafamilial and interfamilial phenotypic heterogeneity associated with lamin A/C defects.